2013
DOI: 10.3201/eid1911.130177
|View full text |Cite
|
Sign up to set email alerts
|

Pseudorabies Virus Variant in Bartha-K61–Vaccinated Pigs, China, 2012

Abstract: The widely used pseudorabies virus (PRV) Bartha-K61 vaccine has played a key role in the eradication of PRV. Since late 2011, however, a disease characterized by neurologic symptoms and a high number of deaths among newborn piglets has occurred among Bartha-K61–vaccinated pigs on many farms in China. Clinical samples from pigs on 15 farms in 6 provinces were examined. The PRV gE gene was detectable by PCR in all samples, and sequence analysis of the gE gene showed that all isolates belonged to a relatively ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
262
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 290 publications
(275 citation statements)
references
References 12 publications
12
262
1
Order By: Relevance
“…The results demonstrated that the Bartha-K61 vaccine could effectively protect against lethal challenge with the traditional PRV SH2010 strain, but not against the emerging PRV variant strain SH2012. These findings are consistent with those of other studies [3,11].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The results demonstrated that the Bartha-K61 vaccine could effectively protect against lethal challenge with the traditional PRV SH2010 strain, but not against the emerging PRV variant strain SH2012. These findings are consistent with those of other studies [3,11].…”
Section: Discussionsupporting
confidence: 83%
“…This suggested that the PR vaccine was not effective against wild-type PR infection. According to recent studies, the causative agent of the outbreak was a PRV variant that showed enhanced pathogenicity [3,7,8,10]. In the present study, the PRV strain SH2012 was isolated in 2012 from an infected pig farm in Shanghai, China that used the typical vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations